2015
DOI: 10.1108/ijph-11-2014-0042
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy and despair in the prison setting

Abstract: It was therefore through the secondary analysis by reverie that the importance of the attendance to aspects of intersubjectivity in prison research emerged. This paper contributes to the therapeutic writings on despair in the prison setting, alongside holding implications for qualitative research in the prison setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Surveys show that more than 10.1 million people worldwide and 220,000 people in Iran are in prison, highlighting the importance of investigating their physical and psychological health. 4,5 Research in prisons has shown that physical and psychological disorders are more prevalent in prisoners than in the general population. At least half of these people have personality disorders, one million of them suffer from severe psychiatric disorders such as mood disorders, posttraumatic stress disorder, or psychosis, and almost all of them experience adjustment disorders due to continuous stress conditions, especially in the presence of secondary alexithymia.…”
mentioning
confidence: 99%
“…Surveys show that more than 10.1 million people worldwide and 220,000 people in Iran are in prison, highlighting the importance of investigating their physical and psychological health. 4,5 Research in prisons has shown that physical and psychological disorders are more prevalent in prisoners than in the general population. At least half of these people have personality disorders, one million of them suffer from severe psychiatric disorders such as mood disorders, posttraumatic stress disorder, or psychosis, and almost all of them experience adjustment disorders due to continuous stress conditions, especially in the presence of secondary alexithymia.…”
mentioning
confidence: 99%
“…Indeed, it is crucial that the MHST psychologist offers specific interventions that have not to be conditioned by secondary benefits for the prisoner (such as single cell allocation, opening of the incarceration armored door, increasing of the pharmacotherapy dosage). In this respect, the general medical staff's mediation is essential for a correct decoding of a prisoner's request and to create a therapeutic setting without specific mandate other than that closely related to psychological treatments (Gee et al, 2015).…”
Section: Detention Phasementioning
confidence: 99%
“…The prison environment has unique conditions and characteristics; in general, prison is one of the most stressful and anxious conditions for any human being. The study of various psychological and behavioral components of prisoners is one of the main topics of interest to psychologists and social scientists [6,7].…”
Section: Introductionmentioning
confidence: 99%